2022
DOI: 10.3390/d14060450
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Plant Diversity along a Watershed in the Semi-Arid Lands of North Africa

Abstract: Plants are a vital part of the world’s biological diversity and have great economic and cultural importance. Plant biodiversity balances ecosystems, protects watersheds, mitigates erosion, affects climate, and provides shelter for many animal species. This study aimed to determine plant diversity in relation to the soil properties of semi-arid rangelands along a gradient at the watershed scale in the Oued Chabro, Algeria. Plants and soil were sampled at 27 points distributed in three sampling sites (upstream, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Amaranthaceae. and Chenopodiaceae were the most representative [30]. Since 1960. the steppe regions of North Africa have been subject to increasing desertification.…”
Section: Discussionmentioning
confidence: 99%
“…Amaranthaceae. and Chenopodiaceae were the most representative [30]. Since 1960. the steppe regions of North Africa have been subject to increasing desertification.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized the minimum area method (GUINOCHET, 1973), which determines the area required for a floristic sample (LACOSTE, SALANON, 2005). This methodology has been applied by various authors, such as Hammada (2007) in the study of Morocco's wetlands vegetation; Hamel et al (2013) regarding the rare and endemic vascular flora of the Edough peninsula (Northeastern Algeria); Zedam (2015) focusing on endemic flora in the Chott El Hodna wetland (North Algeria); Zedam;Fenni (2021) in an advanced research on vascular flora in the highlands of Algeria; Larbi et al (2021) concerning the floristic and phytogeographical diversity of a cedar forest in Djurdjura (North Algeria); and Souahi et al (2022) exploring the variation in plant diversity along a watershed in a semi-arid region (Northeastern Algeria). For each encountered species in any survey, we assigned a semi-quantitative coefficient using the abundance-dominance scale (BRAUN-BLANQUET et al, 1952;GILLET, 2000).…”
Section: Samplingmentioning
confidence: 99%
“…Our study suggested that soil salinity affected the spatial variability of species diversity. This was because soil salinity is one of the most important factors affecting plant distribution in arid desert regions (Chenchouni, 2017;Souahi et al, 2022). The scarce annual precipitation and the high osmotic pressure generated by perennial drought often led to increasing salt concentrations in the soil surface (Souahi et al, 2022), which in turn influenced the distribution of plants and the species composition of communities.…”
Section: Soil Mds Affects Spatial Variability Of Species Diversitymentioning
confidence: 99%
“…This was because soil salinity is one of the most important factors affecting plant distribution in arid desert regions (Chenchouni, 2017;Souahi et al, 2022). The scarce annual precipitation and the high osmotic pressure generated by perennial drought often led to increasing salt concentrations in the soil surface (Souahi et al, 2022), which in turn influenced the distribution of plants and the species composition of communities. It was well known that nutrient availability was one of the main determinants of plant diversity in arid desert regions (Reynolds and Haubensak, 2009).…”
Section: Soil Mds Affects Spatial Variability Of Species Diversitymentioning
confidence: 99%
See 1 more Smart Citation